2021
DOI: 10.1002/advs.202103830
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Lateral Heterostructures of Van Der Waals Crystals with Sharp, Carrier–Transparent Interfaces

Abstract: Research on engineered materials that integrate different 2D crystals has largely focused on two prototypical heterostructures: Vertical van der Waals stacks and lateral heterostructures of covalently stitched monolayers. Extending lateral integration to few layer or even multilayer van der Waals crystals could enable architectures that combine the superior light absorption and photonic properties of thicker crystals with close proximity to interfaces and efficient carrier separation within the layers, potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Solution synthesis has yielded GeSe nanosheets with few micrometer lateral size 16 that could be relatively thick (300-400 nm), 17 as well as thin, long GeSe nanobelts. 18 Vapor transport growth of GeSe flakes should be straightforward since GeSe evaporates as a molecule and has high vapor pressure at relatively low temperatures, similar to other group IV-monochalcogenides, which has allowed the controlled synthesis of GeS 19 and SnS flakes 20,21 as well as heterostructures between them 22,23 under mild conditions. However, vapor transport growth using stoichiometric GeSe as a precursor has been carried out mostly at high source temperatures (T S ) with mixed results to date, including the formation of massive nano-combs (T S = 570 °C), 24,25 sub-μm triangular plates with tens of nm thickness (470 °C), 26 standing hexagonal plates with ∼15 nm thickness and lateral sizes of a few μm (550 °C), 2 and ribbons of a hexagonal GeSe polymorph (550 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Solution synthesis has yielded GeSe nanosheets with few micrometer lateral size 16 that could be relatively thick (300-400 nm), 17 as well as thin, long GeSe nanobelts. 18 Vapor transport growth of GeSe flakes should be straightforward since GeSe evaporates as a molecule and has high vapor pressure at relatively low temperatures, similar to other group IV-monochalcogenides, which has allowed the controlled synthesis of GeS 19 and SnS flakes 20,21 as well as heterostructures between them 22,23 under mild conditions. However, vapor transport growth using stoichiometric GeSe as a precursor has been carried out mostly at high source temperatures (T S ) with mixed results to date, including the formation of massive nano-combs (T S = 570 °C), 24,25 sub-μm triangular plates with tens of nm thickness (470 °C), 26 standing hexagonal plates with ∼15 nm thickness and lateral sizes of a few μm (550 °C), 2 and ribbons of a hexagonal GeSe polymorph (550 °C).…”
Section: Introductionmentioning
confidence: 99%
“…First, the MoS 2 at the top and bottom regions is more laterally extended than at the middle region (Figure 2a,d) This unbalanced MoS 2 growth is different from the uniform growth of multilayer GeS from the edge of multilayer SnS. 40,41 The morphology and growth mechanism of the MoS 2 are discussed in the Supporting Information S5. Second, the present WSe 2 has 2H stacking, and the same stacking structure can also be seen for MoS 2 (Figure 2g−i and S5b,c).…”
Section: Resultsmentioning
confidence: 98%
“…34−38 Furthermore, a similar growth process was extended to multilayerbased in-plane heterostructures of GeS and SnS. 40,41 However, no studies on in-plane heterostructures based on multilayer TMDCs have been reported. Generally, multilayer TMDCs have high carrier mobilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Group IV monochalcogenides (MX, M = Ge, Sn; X = S, Se, Te) are a class of materials that have recently attracted attention in research and various applications. This family of materials is a promising candidate for applications, such as energy conversion devices and phase change memory, , owing to their intriguing electronic, thermoelectric, and ferroelectric properties as well as their unique bonding mechanisms. , The physical properties of group IV monochalcogenides show a strong correlation with the types of chalcogen atoms (S, Se, and Te). For example, Ge and Sn monochalcogenides with S and Se exhibit semiconducting properties, whereas monochalcogenides with Te have a small bandgap and exhibit high doping concentrations. , Furthermore, alloying of different chalcogenides has also been pursued to control the physical properties of this material system. ,, …”
mentioning
confidence: 99%